Reducing Motion Sickness When Reading With Head-Mounted Displays By Using See-Through Background Images - Suwa, Tsukasa; Sato, Yuki; Wada, Takahiro (Frontiers in Virtual Reality, 2022)
With the development of virtual reality technology, head-mounted displays (HMDs) have been increasingly used to view or read 2D content while in vehicles. When 2D content is displayed in a fixed position on an HMD, the visual appearance does not change even with head movements, and body movements cannot be perceived while watching 2D content. This may cause visual-vestibular conflict and severe motion sickness. This study investigates whether motion sickness when reading 2D content fixed to the HMD coordinate system can be reduced by allowing readers to perceive body movements through video see-through images obtained from the front camera of the HMD in situations where the body vibrates. Twenty participants performed 20-minute reading tasks in which they read a book fixed to the HMD coordinate while seated in a vibration device. Two background conditions of the book were explored: (1) the white background condition—not allowing participants to perceive their movements visually, and (2) the camera background condition—allowing participants to perceive their movements visually through see-through images. Evaluation of motion sickness using Misery Scale, which is an 11-point questionnaire, showed that motion sickness after task completion was significantly lower in the camera background condition than in the white background condition. This result suggests that the sensory conflict between visual and vestibular sensations can be reduced, and motion sickness can be relieved, provided that the users perceive their motion in the peripheral vision through the camera image, even if they gaze at 2D content fixed in the HMD coordinate system in the central vision. This study helps promote the use of HMDs by alleviating motion sickness.